ابتكار المواهب وصقلها في ضوء السيرة النبوية: Creating & refining the talents in the light of Seerah of the Holy Prophet PBUH - Dr. Kafait Ullah Hamdani (Seerat Studies, 2023)
The Prophet Hazrat Muhammad SAAW is the greatest and noblest teacher, the world has ever seen. The Quran proclaims that he was chosen by Allah as mercy to all creations, an excellent role model who was possessed of the most exalted character. He successfully taught and conveyed the message of Islam to the people of Arabia and inculcated the basic qualities of morality & leadership in his companions. He innovated and refining the talents and basic characteristics in his friends and students. This article deals with the principles related to human relations, the researchers made the biography of the Prophet Hazrat Muahmmad SAAW a basis and role model for deducing and deriving the principles of relationships; the principle of discovering capabilities, the principle of choosing the right person for right job, the principle of appreciating potentials. The method used for this research was deductive, analytical and applied. The purpose of this study is to highlight the prophetic approach in creating and refining the talent of the companions. This article found the excellent examples & results in this regard.